Dual-Field-of-View Depolarization approach using the PollyXT Raman Lidar: Characterization of aerosol-cloud interactions in the semi-arid climate of Cyprus - Chrysostomou, Charalambos; Jimenez, C.; Mamouri, Rodanthi-Elisavet; Nisantzi, Argyro; Hadjimitsis, Diofantos G.; Ansmann, Albert (My University, 2025)
Aerosols are a key parameter when referring to atmospheric studies or advanced climate research. Their role in influencing Earth's energy balance or the formation, lifetime and evolution of clouds has long been studied, but no clear conclusion on their contribution to climate forcing has yet emerged. This leaves us with high uncertainties in both the aerosol-radiation interactions (ARI), as well as in aerosol-cloud interactions (ACI). The latter one especially, exhibits one of the largest uncertainties among all the forcing parameters. According to the Fifth Assessment Report (AR5) of IPCC, the radiative forcing of aerosol-cloud interactions was estimated as -0.45 W/m2 with uncertainties ranging from -1.2 to 0 W/m2, whereas the last report (AR6) of IPCC refined these numbers to -0.7 ± 0.5 W/m2, highlighting in both cases that these values rely on moderate and not high confidence [1], [2]. This last statement showcases how important it is for extensive, detailed, and in-depth studies of these interactions to be conducted now more urgently than ever, as these significant uncertainties arise due to the incomplete understanding of how clouds develop during certain aerosol and weather conditions. The novel Dual-Field-of-View (DFOV) polarization lidar approach, developed by C. Jimenez et al., 2020, comes as a competent solution to the aforementioned challenges [3]. This method works just by using lidar’s data and is able to provide crucial information about the microphysical properties of liquid-water, or even, mixed phase clouds. Properties such as the Cloud Droplet Number Concentration (Nd), their effective radius (Re), the cloud extinction coefficient (α), and the Liquid Water Content (LWC). Additionally, by using products like the quasi backscatter coefficient and by implementing Doppler Lidar’s data, the cloud condensation nuclei (CCN) concentration and the vertical wind below the cloud base can be retrieved, and therefore, the influence of certain type of aerosols and their concentration in relation also to the behavior of the wind, can yield to an unprecedent view of aerosol-cloud interactions. In this study, data acquired by the Cyprus Atmospheric Remote-Sensing Observatory (CARO) National Facility of the Eratosthenes Centre of Excellence, and more precisely by the PollyXT Raman Lidar and the Halo Photonics (Snoopy) Doppler Lidar, are used to analyze cases of liquid-water or mixed-phase clouds in Limassol. By applying the DFOV Depolarization approach on these cases, cloud properties are able to accurately be retrieved for the first time in the region of Eastern Mediterranean, Middle East and Northern Africa (EMMENA), further contributing to ACI studies.